2008
DOI: 10.1116/1.2884752
|View full text |Cite
|
Sign up to set email alerts
|

Molecular beam epitaxy grown Ga2O3(Gd2O3) high κ dielectrics for germanium passivation-x-ray photoelectron spectroscopy and electrical characteristics

Abstract: Molecular beam epitaxy deposited Ga2O3(Gd2O3) on Ge, without a commonly employed interfacial layer of GeON, has demonstrated excellent electrical properties, such as a high κ value of 14.5, a low electrical leakage current density, and well behaved C-V characteristics even being subjected to 500°C annealing in N2 ambient for 5min. In situ angle-resolved x-ray photoelectron spectroscopy (XPS) studies have revealed an abrupt Ga2O3(Gd2O3)∕Ge interface without forming any interfacial layer. Further XPS studies exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…2(a)). This indicates the existence of extra bonds of Ge, introduced by the slight Ge interdiffusion during oxide deposition that has also been observed in our previous work [11]. Y 3d core-level spectra ( Fig.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…2(a)). This indicates the existence of extra bonds of Ge, introduced by the slight Ge interdiffusion during oxide deposition that has also been observed in our previous work [11]. Y 3d core-level spectra ( Fig.…”
Section: Resultssupporting
confidence: 52%
“…CET is defined as Fig. 3(a)) has been achieved at a gate bias of V fb +1 V, which compares favorably with the previously measured leakage currents using MBE-Al 2 O 3 / Ga 2 O 3 (Gd 2 O 3 ) on Ge [11]. Compared to those with other commonly used dielectrics, such as GeO x N y [12], GeO x N y plus HfO 2 [1,[13][14][15], Si plus HfO 2 [16,17], and HfO 2 [18], several orders of reduction in leakage current density are attained in this work, as shown in Fig.…”
Section: Resultsmentioning
confidence: 87%
“…In particular, GGO/Ge is thermally stable, having a minimum Ge inter diffusion sustaining a rapid thermal annealing to 550 C, as confirmed by high resolution transmission electron microscopy and angle-resolved X-ray photoelectron spectroscopy (XPS) analysis. 12,13) Moreover, GGO/Ge p-channel MOS field-effect-transistors (pMOSFETs) have an effective mobility of 390 cm 2 V À1 s À1 , a maximum drain current of $500 A/m, and a peak transconductance of $180 S/m. 13) In this letter, we focused on the key issue of the highdielectrics on Ge, namely, interfacial density of states (D it ) and its distribution within the Ge band gap.…”
mentioning
confidence: 99%
“…12,13) Moreover, GGO/Ge p-channel MOS field-effect-transistors (pMOSFETs) have an effective mobility of 390 cm 2 V À1 s À1 , a maximum drain current of $500 A/m, and a peak transconductance of $180 S/m. 13) In this letter, we focused on the key issue of the highdielectrics on Ge, namely, interfacial density of states (D it ) and its distribution within the Ge band gap. The D it spectrum in the upper half of the Ge band gap for GGO/Ge was obtained using charge pumping (CP) technique at room temperature, and the conductance-voltage (G-V ) as well as conductance-frequency measurements at various low temperatures.…”
mentioning
confidence: 99%
“…To overcome this problem, various techniques including NH 3 surface treatment [2][3][4][5] and Si interlayer [11,12] have been applied in Ge-based MOS devices to enhance device performances. Recently, it was reported that rare-earth metal oxides such as CeO 2 [13,14], Gd 2 O 3 [15] and Dy 2 O 3 [16] produced promising electrical properties when directly in contact with Ge. Especially, La 2 O 3 thin film shows many advantages, including low interface-states density, very small frequency dispersion and hysteresis due to formation of stable lanthanum germanate (La-Ge-O) [16][17][18].…”
Section: Introductionmentioning
confidence: 99%